Mr. Terupt falls again - Buyea, Rob (Buyea, Rob. Mr. Terupt, 2013)
When six friends begin their sixth grade year, they realize their teacher is once again Mr. Terupt. With his help, they navigate the personal challenges that come their way and learn to be the best they can be.